Research Spotlight - Radioimmunotherapy: optimizing delivery to solid tumors. (May 2011) - Rajkumar, Vineeth; Dearling, Jason L; Packard, Alan; Pedley, R Barbara
Radioimmunotherapy (RIT) is a cancer treatment that exploits the specific targeting capability of monoclonal antibodies to deliver cytotoxic radionuclides to antigen-expressing tumor cells or stromal targets. While this has been extremely successful in the treatment of hematologic malignancies, RIT of solid tumors has produced less prolonged effects. In our laboratory, we have developed a bench-to-bedside translational pipeline with the aim of optimizing RIT for solid tumors. We will show how preclinical models of colorectal adenocarcinoma were initially used to study reciprocal interactions between elements of the tumor microenvironment and RIT and to test novel therapeutic strategies. These studies were then used to facilitate the design of novel trials carried out in close collaboration with our clinical colleagues.